Two horizontal root fractures of a permanent central incisor tooth: A case report - Guoying Lu; Xiuqing Wang; Jia Hu; Yuemin Chen; Xiaojing Huang (Heliyon)
Traditionally, teeth with horizontal root fractures resulting in pulp infections have been managed with conventional root canal therapy; however, this technique is associated with a limited success rate. This study presents an unusual case of multiple horizontal root fractures of the maxillary central incisor caused by a traumatic injury. The preservation of vital dental pulp is advantageous for healing root fractures. Therefore, we performed a pulpotomy to maintain vitality of the root pulp. The tooth exhibited no clinical symptoms and regained its normal color. In cases of traumatic root fractures, prompt treatment is important once pulpitis is confirmed. Pulpotomy is highly recommended as this procedure preserves the remaining vital root pulp, thereby enhancing the potential for improved healing. The purpose of this study was to emphasize the difficulty associated with diagnosing multiple root fractures and the value of preserving the biological tissue.